CAPITAL EXPENDITURE EVALUATION BY DIRECT DISCOUNTING. - Gregory, John C. (The Accounting Review, 1962)
Abstract The discount system of capital expenditure evaluation, as the measure of a project's inherent desirability, provides rates of return which can be compared with those of other projects and with another measure, representative of the outside community's charge for the use of savings, called the cost of capital. The author classifies projects into two classes, independent and dependent, in order to discuss the effect of the two capital evaluation methods on each of the two classes of projects. By reviewing the capital expenditures evaluation problem in a number of areas, he finds that the method of direct discounting always provides superior results to those of the rate of return system. Direct discounting more quickly evaluates single-answer independent projects. It solves single-answer dependent projects without analysis of difference projects and without providing misleadingly higher answers on inferior projects. This research paper thus shows that it is simpler and more useful to discount all projects at the cost of capital than to solve for rates of return.